2003
DOI: 10.1890/0012-9658(2003)084[0991:zmsrvl]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Zooplankton Metacommunity Structure: Regional vs. Local Processes in Highly Interconnected Ponds

Abstract: Local communities can be structured by both local interactions (competition, predation, environmental variables, etc.) and by regional interactions (dispersal of individuals between habitats). Using data from a three‐year study on 34 neighboring ponds in an interconnected pond system, we tested whether zooplankton communities show a metacommunity structure, how much variation in zooplankton community structure is related to local environmental factors vs. spatial configuration (taking into account the dispersa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
354
8
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 360 publications
(391 citation statements)
references
References 55 publications
27
354
8
2
Order By: Relevance
“…Local colonization of this group is related to its ability to reproduce asexually (Smith, 1986), and producing cocoons buried in sediment (Lazim et al, 1989) that can tolerate adversity imposed by catastrophic events (for example, flood and drought). Thus, dispersal may act as a structuring force, leading to a constant flow of propagules; then closely connected sites harbor more similar assemblages than sites further apart (Cottenie et al, 2003). These aspects also support our findings, once assemblages of the First, Second, and Third Plateaus were similar within a plateau, rather than between plateaus.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Local colonization of this group is related to its ability to reproduce asexually (Smith, 1986), and producing cocoons buried in sediment (Lazim et al, 1989) that can tolerate adversity imposed by catastrophic events (for example, flood and drought). Thus, dispersal may act as a structuring force, leading to a constant flow of propagules; then closely connected sites harbor more similar assemblages than sites further apart (Cottenie et al, 2003). These aspects also support our findings, once assemblages of the First, Second, and Third Plateaus were similar within a plateau, rather than between plateaus.…”
Section: Discussionsupporting
confidence: 87%
“…Species respond distinctively along environmental gradients at various spatial scales (Cottenie 2005;Heino et al, 2007), and invertebrate communities in lotic systems may be structured along resource gradients from the headwaters to the mouths (Vannote et al, 1980). This gradient may be disrupted by the construction of dams, especially downstream, as predicted by the serial discontinuity concept (Ward and Stanford, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…For both datasets separately, we determined the relative importance of environmental characteristics and spatial processes in explaining differentiation in BCC by decomposing the total variation in the bacterial community matrix into unique environmental and spatial components with corresponding P values using (partial) redundancy analysis (23,37,38). This multivariate extension of linear regression with corresponding R 2 measures the amount of variation (computed as the percentage of the total variation in the community matrix) that can be attributed exclusively to one or the other set of explanatory environmental (E) or spatial (S) variables.…”
Section: Methodsmentioning
confidence: 99%
“…The second dataset consists of bacterial communities of 11 lakes in a strongly interconnected pond system that encompasses 34 small shallow lakes on a total area of Ͻ300 ha (SI Fig. 3) (23). We used a 16S rRNA gene-based fingerprinting technique, denaturing gradient gel electrophoresis (DGGE), to determine BCC.…”
mentioning
confidence: 99%
“…2 and 3 differ, however, in one important aspect: the natural systems were either directly contiguous with other water masses (e.g., the ocean basins) or frequently connected to river channels (the lake basins) that can provide a constant inflow of potential colonists through advection or fluvial inputs. Cottenie et al (19) and Chase and Ryberg (20) have demonstrated that metacommunity structure and propagule subsidies can modify the composition and species diversity of animal communities within ponds located within single watersheds, despite the presence of strong differences in local-scale environmental conditions, and it is very likely that this mechanism can similarly influence natural phytoplankton communities.…”
Section: [3]mentioning
confidence: 99%